B64. Mechanistic Advances in Lung Fibrosis 2020
DOI: 10.1164/ajrccm-conference.2020.201.1_meetingabstracts.a4025
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Signatures of Lung Fibroblast Populations in Development and Fibrosis in Mice and Men

Abstract: Lung fibroblasts have shown high heterogeneity in both mouse and human during lung development and disease states, but no common consensus has been determined. METHODS: In the present study, we performed single cell RNA-sequencing (scRNA-seq) on mouse lung of different stages. We extracted scRNA-seq data of both mouse lung of different stages and normal and IPF lung from published studies. RESULTS: We profiled 7,477 cells from three E17.5 embryonic mouse lungs, and 2,002 mesenchymal cells were readily clustere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…6C). Consistent with this finding, we noted upregulation of Runx1 , a transcription factor recently described to regulate the differentiation of fibroblasts into myofibroblasts, which produce matrix proteins, thus contributing to fibrosis 80 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…6C). Consistent with this finding, we noted upregulation of Runx1 , a transcription factor recently described to regulate the differentiation of fibroblasts into myofibroblasts, which produce matrix proteins, thus contributing to fibrosis 80 .…”
Section: Resultssupporting
confidence: 88%
“…Volcano plot comparing iDIF to DIF in HOX shows significantly increased expression of TGFB signaling and its downstream genes ( Pdgfrb , Ccnd1 , Col12a1 , Runx1 , Timp1 ) 7579 , and less expression of Inmt , a gene enriched in DIF (Fig. 6B) 80 . DIF, as lipid storing fibroblasts, provide lipids to AT2 cells for surfactant production 81 .…”
Section: Resultsmentioning
confidence: 99%
“…Lung lipofibroblasts, local equivalents of lung adipocytes, express common adipocyte genes, including Pparg, Plin2, Fabp1, Fabp4, Fabp5, Lpl, and Lipa and also demonstrate the ability to dedifferentiate into myofibroblasts and contribute to lung fibrosis [11 ▪▪ ,12 ▪▪ ]. They are differentiated from lung fibroblast progenitors, expressing platelet derived growth factor receptor and are able to dynamically transdifferentiate between myofibroblast and lipofibroblast upon stimuli [13].…”
Section: Direct Contribution Of Adipose Tissue To Systemic Sclerosis ...mentioning
confidence: 99%
“…In healthy and idiopathic pulmonary fibrosis tissue, Liu et al . were able to describe the lipofibroblast population, however observed that canonical lipofibroblast markers were ineffective in identifying lipofibroblast clusters in human lung and proposed TCF21 as a new lineage marker for lipofibroblasts [12 ▪▪ ]. This finding may explain the difficulty in identifying human lung fibroblasts in vivo using conventional marker genes.…”
Section: Direct Contribution Of Adipose Tissue To Systemic Sclerosis ...mentioning
confidence: 99%